PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DENGAN MEDIA HIDDEN CHART UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 67 PEKANBARU - Fitri Islami; Mahmud Alpusari; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is based on the low grade of fifth grader’s science learning in SDN 67 Pekanbaru, seen from minimum criteria of mastery that defined by school policy is 75. 15 students of 27 in total did not achieve minimum criteria, with average grade value is 61,30. This condition is caused by the teacher learning method is lack of variaton. Beside, teacher does not use creative media in learning process. Those things make students lack of motivation and barely understand what they learn. Due to these issues, the action taken is cooperative learning with hidden chart media. The purpose of this research is to improve students’ science grade. The form of this research is a class action research. The subjects are VC class students in SDN 67 Pekanbaru, consist of 27 students; 16 male and 11 female. Research instruments are test sheets, teacher and students observation sheets, and documentation files. The results showed improvement from each cycle. Teacher’s activities in first cycle was 70,83%, and increase to 79,17%. In second cycle was 91,67%, and increase to 95,83. Students’ activities in first cycle was 62,50%, and increase to 75%. In second cycle was 83,33%, and increase to 87,50%. Students’ average grade showed improvement too. Base grade was 61,30; increased to 72,15 on first test, and increased to 79,41 on second test. Based on these results, can be concluded that application of cooperative learning with hidden chart media can improve students’ science grade of VC class in SDN 67 Pekanbaru.Keyword : Cooperative learning, hidden chart media, science grade.